Forest diversity and modeling diameter distribution of the tropical dryforest in East Nusa Tenggara, Indonesia - Almulqu, Aah Ahmad (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2021)
The variation of forest conditions shows structural differences, species composition, and potential value as well as stand density. The need and important role of stand structure model in forest management, particularly in forest-based product regulation become the supply demands quantitatively for various forest conditions in Indonesia. The objective of the study was to determine the stand structure model of dry forest. The study was conducted at the dry forest of Binafun, Bonmuti, Letkole and Oelbanu, East Nusa Tenggara Province. Determination of the best stand structure model based on maximum likelihood function of family distribution that tested including the function of exponential, gamma, lognormal and Weibull. A total of 2097 tree individuals, its representing 94 species, 72 genera and 45 families, were found in the research sites. Eucalyptus urophylla were found to be the most dominant species in the research sites and Elattostachys verrucosa have potential to replace Dryobalanops aromatic. Most of family distribution models can describe the stand structure in research sites. The models presented here are the basis for further developments toward the tree diversity for general purpose in tropical dry forest management of East Nusa Tenggara, Indonesia.